Laparoscopic Peritoneal dialysis catheter insertion and its outcome in a cohort of automated peritoneal dialysis patients. - Ashraf, Shahzad; Qayyum, Ahad; Saleem, Muhammad; Rehan, Irtiqa; Hussain, Sadia; Riaz, Wardah; Pervaiz, Haroon (Pakistan Journal of Kidney Diseases, 2025)
Background: Reliable peritoneal dialysis (PD) access is critical to technique survival. We describe early outcomes from a single-center series of PD catheter insertions and summarize durations and reinsertion events. Methods: Consecutive patients undergoing PD catheter placement were analysed. The primary outcome was any catheter reinsertion or documented malfunction. Durations from index insertion to 1 September 2025 were computed. Descriptive statistics were generated. Results: Among 21 patients (mean age 54.9±18.9 years), laparoscopic placement was used in 21 cases. Reinsertion/malfunction occurred in 4 (19.0%). Mean duration was 260.2±169.6 days; median 235 (range 10-601). Duration categories: ≤30 days: 2 (9.5%), 31–90 days: 2 (9.5%), 91–180 days: 2 (9.5%), >180 days: 15 (71.4%). Conclusions: Laparoscopically placed PD catheter resulted in an overall successful maintenance of PD catheter short term and long term. Further long term studies are needed for a local experience in PD catheter placement laparoscopically and a comparative analysis with other techniques.